Three-dimensional changes in cystic lesions of the mandible after marsupialization - Tomomatsu, Nobuyoshi; Takahara, Namiaki; Kurasawa, Yasuhiro; Terauchi, Masahiko; Iwasaki, Takuya; Yoda, Tetsuya (Journal of Oral and Maxillofacial Surgery, Medicine, and Pathology, 2022)
Cysts of the mandible are common and are often found clinically in oral surgery. Marsupialization for relatively large cystic lesions may be performed to reduce the size of the lesion and to obtain a histopathological diagnosis. For cystic lesions of the mandible, the effect of marsupialization has many advantages, such as a reduction in lesion size, the avoidance of mental nerve palsy, and preservation of the teeth. It is still unclear whether there is a difference in the reduction rate based on patient age and pathology (dentigerous cyst, odontogenic keratocyst, radicular cyst, ameloblastoma (unicystic type)) and initial size of the lesion. The subjects included 55 patients with cystic lesions with a major axis of 3 cm or greater (16 dentigerous cysts, 20 odontogenic keratocysts, 7 radicular cysts, and 12 ameloblastoma) who underwent treatment at our department. Using simulation software (ProPlanCMF®), the volume of the lesion was extracted from the CT data before and after the marsupialization, and the three-dimensional reduction rate before and after marsupialization was calculated. No significant difference was observed between the subgroups in terms of histopathological diagnosis, patient age or size of lesion. Although the effect of marsupialization on cystic lesions with a major axis of 3 cm or more showed a significant difference between 3.0 months and 4.5 months, the difference was not significant between 4.5 months and 6.0 months. An indication for the enucleation timing after marsupialization is 4.5 months when the rate of decrease after fenestration slows down.